KONSTRUK TAKSONOMI SOLO DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM - Erwinsyah, Alfian (Irfani, 2025)
This article aims to explore the potential of the SOLO Taxonomy (Structure of Observed Learning Outcomes) as a framework to improve the quality of learning and assessment of Natural Sciences (IPA), especially in encouraging deep conceptual understanding (deep learning) and high-level thinking skills (HOTS). Using narrative literature review with a qualitative approach to analyze three dimensions: (1) The epistemological relevance of SOLO to the complexity of science, (2) Evidence of implementation in learning/assessment design, and (3) Operational challenges of its implementation. The synthesis of data is sourced from scientific journals, textbooks, and the latest empirical studies. The results are that SOLO (based on five levels: Pre-Structural to Abstract Extended) has proven to be effective in Authentic Assessment, i.e. Measuring students' cognitive structure and HOTS more accurately than conventional assessments. The Instructional Guide i.e. Scaffolding (e.g., concept map, analogy) successfully guides students towards systemic thinking (Relational-Abstract level). Implementation challenges, namely the subjectivity of teacher assessment and the difficulty of applying abstract levels, are overcome through collaborative training, SOLO templates, and technology (e-rubric, AI). The implication is that SOLO shifts the focus of learning from the product (correct answer) to the process of knowledge construction.